Our subway baby - Mercurio, Peter (Dial Books for Young Readers, 2020)
""Some babies are born into their families. Some are adopted. This is the story of how one baby found his family in the New York City subway." So begins the true story of Kevin and how he found his Daddy Danny and Papa Pete. Written in a direct address to his son, Pete's moving and emotional text tells how his partner, Danny, found a baby tucked away in the corner of a subway station on his way home from work one day. Pete and Danny ended up adopting the baby together. Although neither of them had prepared for the prospect of parenthood, they are reminded, "Where there is love, anything is possible."" -- Amazon.com